2000
DOI: 10.1111/j.1528-1157.2000.tb00291.x
|View full text |Cite
|
Sign up to set email alerts
|

Autonomic Seizures Versus Syncope in 18q‐ Deletion Syndrome: A Case Report

Abstract: Summary: Purpose: The 18q‐ deletion syndrome (18qDS) is frequently associated with cardiac anomalies. Patients with this syndrome may also have epilepsy, which presents certain diagnostic difficulties. This case report aims to illustrate these diagnostic problems, document the usefulness of heart rate‐based seizure detection algorithms in this setting, and define the epilepsy syndrome associated with 18qDS. Methods: Closed‐circuit video electroencephalogram (EEG) monitoring using a heart rate–based seizure d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
11
0
1

Year Published

2002
2002
2008
2008

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 10 publications
1
11
0
1
Order By: Relevance
“…Although one review of the neurological manifestations of 18q-syndrome stated that "a substantial minority of patients have epilepsy" [6], we have identified few published reports [4,[9][10][11]. This is in keeping with a review of over 400 different chromosomal imbalances associated with seizures or EEG abnormalities which reported that "seizures have not been well-described in 18q syndrome" [7].…”
supporting
confidence: 65%
See 1 more Smart Citation
“…Although one review of the neurological manifestations of 18q-syndrome stated that "a substantial minority of patients have epilepsy" [6], we have identified few published reports [4,[9][10][11]. This is in keeping with a review of over 400 different chromosomal imbalances associated with seizures or EEG abnormalities which reported that "seizures have not been well-described in 18q syndrome" [7].…”
supporting
confidence: 65%
“…Nonetheless, seizure disorders have only rarely been described in 18q-syndrome [4,[9][10][11], mostly in those of childhood onset. As this condition may be unfamiliar to neurologists working with adult patients, we report a patient with 18q-syndrome with complex partial seizures of adult onset.…”
mentioning
confidence: 99%
“…An unspecified type of epilepsy was also reported in a girl with an atypical Rett syndrome carrying an interstitial deletion of chromosome 18(q21.1q22.3) [Gustavsson et al, 1999]. By contrast, Sturm et al [2000] reported an adult patient carrying an 18q21.3 deletion, presenting with autonomic seizures related to the insular/ temporal lobe, and well controlled with CBZ. Kumada et al [2003] reported an infant with 18qDS having CPS with apneic attacks.…”
Section: Discussionmentioning
confidence: 80%
“…Seizures have not been well described in 18q syndrome, with the exception of one report of complex partial seizures with prominent autonomic manifestations that could be confused with syncope (189).…”
Section: Chromosomes 18 and 19mentioning
confidence: 99%